Creating character arcs : the masterful author's guide to uniting story structure, plot, and character development - Weiland, K. M. (PenForASword Publishing, 2016)
Explores the techniques of effective character development in the processing of writing novels to take the author's stories from good to great, including how to determine which arc is right for your character, why you should never pit plot against character, and how to avoid the pitfalls of writing novels without character arcs.